Exploring English Teachers’ Pedagogical Wellbeing and Classroom Issues: A Narrative Inquiry - Bastola, Ganesh Kumar (Educational Journal, 2023)
This paper deals with the classroom issues of English as a Foreign Language (EFL) teaching in the context of Nepal and the EFL teachers' ways of addressing them. More specifically, it connects how pedagogical strengths help teachers address the issues that appear in language classrooms. The research has been carried out outlining the qualitative approach grounded in an interpretive research paradigm. The data were collected from three university teachers. Methodologically, the study adopts the three-dimensional narrative spaces as the prior procedures of research methods for theoretical insight. It concludes that teachers' profound knowledge and skills about their well-being are useful to integrate various cultures and content in the classrooms. Pedagogically inbuilt potentials of teachers maximally enhance learners' learning opportunities. Thus, the conclusion obtained in this study is assessed considering teachers' understanding, of classroom issues and their ways of addressing those problems but they may not be generalizable. However, it contributes to teachers' education in general and ELT practice in Nepal in particular.